Oxygen-rich cobalt–nitrogen–carbon porous nanosheets for bifunctional oxygen electrocatalysis - Zhang, Wang (2022)
Metal–nitrogen–carbon (M–N–C) materials have attracted much interest in bifunctional oxygen-involving electrocatalysis for rechargeable Zn–air batteries. Such M–N–C electrocatalysts with M–Nx sites show good activity for the oxygen reduction reaction (ORR) but moderate activity for the oxygen evolution reaction (OER). Herein, an oxygen-rich M–N–C material (O–Co–N/C) with a highly porous nanosheet structure is reported as a bifunctional oxygen electrocatalyst, which is prepared by the direct pyrolysis of ultrathin CoO nanosheets decorated with zeolitic imidazolate framework-8 nanoparticles under an inert atmosphere. Particularly, Co nanoparticles in the O–Co–N/C electrocatalyst contain both Co–Nx and Co–Ox coordination environments to provide intrinsic active sites for the ORR and OER, respectively. Furthermore, electrochemical studies show that the O–Co–N/C catalyst retains comparable ORR activity to common M–N–C materials with a half-wave potential of 0.85 V vs the reversible hydrogen electrode and better OER activity with an overpotential of 0.29 V at the current density of 10 mA cm−2. This study provides insights into the development of effective oxygen-involving electrocatalysts with bifunctional metal active centers coordinated by both nitrogen and oxygen atoms.